1994
DOI: 10.1088/0022-3727/27/11/019
|View full text |Cite
|
Sign up to set email alerts
|

Performance of a 16.7 m air rod-plane gap under a negative switching impulse

Abstract: Experimental results of the development of a negative discharge in a 16.7 m rod-plane air gap are presented. Similarities with the cloud-to-earth discharge are found and some characteristic parameters are compared. Use of an image converter linked to two still cameras allows quite accurate analysis of the discharge propagation. Information relative to the space leader inception is provided. The current pulse shapes are related to the mechanisms of propagation and the thermal channel diameter of the discharge i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
55
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(64 citation statements)
references
References 3 publications
8
55
1
Order By: Relevance
“…It may be concluded from the figure that, for the range of characteristics tested, longer insulator lengths result in a higher current during propagation. This tendency was also observed for electrical breakdown in air gaps [114].…”
Section: Propagating Arcsupporting
confidence: 68%
See 1 more Smart Citation
“…It may be concluded from the figure that, for the range of characteristics tested, longer insulator lengths result in a higher current during propagation. This tendency was also observed for electrical breakdown in air gaps [114].…”
Section: Propagating Arcsupporting
confidence: 68%
“…Figure 6.22 indicates the effects of the above-mentioned parameters on arc velocity, from which it may be concluded that, for the range of characteristics tested, longer insulator lengths result in higher maximum velocities during arc propagation. This tendency was also observed for electrical breakdown in air gaps [114]. Wider ice bands and higher applied water conductivities will also result in higher maximum velocities.…”
Section: Arc Currentsupporting
confidence: 54%
“…The average stepping period results between 15 and 20 µs. The calculated current is composed by a series of pulses which are consistent with current measurements [33].…”
Section: Negative Dischargementioning
confidence: 53%
“…The negative space leader extremity becomes the new leader head and the process is repeated [Bazelyan and Raizer, 1998, p. 255]. The formation of a space leader ahead of the negative leader is a fundamental stage in the leader progression, as evidenced in laboratory [e.g., Ortega et al, 1994;Reess et al, 1995;Bazelyan and Raizer, 1998;Gallimberti et al, 2002] and lightning [e.g., Biagi et al, 2009Biagi et al, , 2010Hill et al, 2011] observations. Although positive and negative leaders exhibit different dynamical features, it can be seen, from the above discussion, that the streamer-to-leader transition (or in other words, the air heating) is a fundamental process that defines leader propagation in both cases.…”
Section: Phenomenology Of Positive and Negative Leadersmentioning
confidence: 99%